Mekanisme Ekstrak Daun Salam (Syzygium Polyanthum) sebagai Antidiabetes - Mexsi Mutia Rissa (Jurnal Health Sains, 2022)
Diabetes mellitus is a condition in which the pancreas cannot produce enough insulin for the body. The number of people with diabetes mellitus is estimated to continue to increase around 578 million people in 2030. Management of diabetes mellitus is through pharmacological and non-pharmacological therapies. Pharmacological therapy is considered quite expensive and causes side effects, so they started to switch to using herbs, including bay plants. Bay leaves have antidiabetic activity, containing flavonoids. The purpose of this study was to summarize the mechanism of bay leaf extract (Syzygium Polyanthum) as an antidiabetic in several scientific articles. The method used in this article review is to conduct a literature study on scientific articles published in 2011-2021, in English or Indonesian, and pre-clinical trials. This journal search strategy was carried out using keywords: "Syzygium polyanthum, diabetes mellitus, hypoglycemic, hyperglycemic". There are 5 articles that are appropriate and reviewed. The results of the review show that bay leaf extract has activity in lowering blood sugar through several mechanisms, inhibiting ROS (Reactive Oxygen Species) free radicals through electron transfer and inhibiting peroxidation reactions. The conclusion of this study is that bay leaves have antidiabetic activity through the mechanism of inhibiting free radicals of ROS (Reactive Oxygen Species).